Association between Red Blood Cell Distribution Width and Coronary Artery Calcification in Patients Undergoing 64-Multidetector Computed Tomography - Gürel, Ozgul Malcok (Korean Circ J, 2015)
BACKGROUND AND OBJECTIVES: The red blood cell distribution width (RDW) has been found to be associated with cardiovascular morbidity and mortality. The objective of this study was to determine whether the RDW measures are associated with the coronary artery calcification score (CACS) in patients who did not present with obvious coronary heart disease (CHD). SUBJECTS AND METHODS: A total of 527 consecutive patients with a low to intermediate risk for CHD but without obvious disease were enrolled in this study. The study subjects underwent coronary computerized tomography angiography and CACS was calculated. The patients were divided into two groups based on CACS: Group I (CACS≤100) and Group II (CACS>100). The two groups were compared in terms of classic CHD risk factors and haematological parameters, particularly the RDW. RESULTS: Group I patients were younger than Group II patients. The Framingham risk score (FRS) in patients of Group II was significantly higher than that in patients of Group I. Group II patients had significantly elevated levels of haemoglobin, RDW, neutrophil count, and neutrophil/lymphocyte ratio compared with Group I patients. CACS was correlated with age, RDW, and ejection fraction. In the multivariate analysis, age, RDW, and FRS were independent predictors of CACS. Using the receiver-operating characteristic curve analysis, a RDW value of 13.05% was identified as the best cut-off for predicting the severity of CACS (>100) (area under the curve=0.706). CONCLUSION: We found that the RDW is an independent predictor of the CACS, suggesting that it might be a useful marker for predicting CAD.